Modulation of the Response to Mycobacterium leprae and Pathogenesis of Leprosy - Cabral, Natasha; de Figueiredo, Vilma; Gandini, Mariana; de Souza, Cíntia Fernandes; Medeiros, Rychelle Affonso; Lery, Letícia Miranda Santos; Lara, Flávio Alves; de Macedo, Cristiana Santos; Pessolani, Maria Cristina Vidal; Pereira, Geraldo Moura Batista (Frontiers in Microbiology, 2022)
The initial infection by the obligate intracellular bacillus Mycobacterium leprae evolves to leprosy in a small subset of the infected individuals. Transmission is believed to occur mainly by exposure to bacilli present in aerosols expelled by infected individuals with high bacillary load. Mycobacterium leprae-specific DNA has been detected in the blood of asymptomatic household contacts of leprosy patients years before active disease onset, suggesting that, following infection, the bacterium reaches the lymphatic drainage and the blood of at least some individuals. The lower temperature and availability of protected microenvironments may provide the initial conditions for the survival of the bacillus in the airways and skin. A subset of skin-resident macrophages and the Schwann cells of peripheral nerves, two M. leprae permissive cells, may protect M. leprae from effector cells in the initial phase of the infection. The interaction of M. leprae with these cells induces metabolic changes, including the formation of lipid droplets, that are associated with macrophage M2 phenotype and the production of mediators that facilitate the differentiation of specific T cells for M. leprae-expressed antigens to a memory regulatory phenotype. Here, we discuss the possible initials steps of M. leprae infection that may lead to active disease onset, mainly focusing on events prior to the manifestation of the established clinical forms of leprosy. We hypothesize that the progressive differentiation of T cells to the Tregs phenotype inhibits effector function against the bacillus, allowing an increase in the bacillary load and evolution of the infection to active disease. Epigenetic and metabolic mechanisms described in other chronic inflammatory diseases are evaluated for potential application to the understanding of leprosy pathogenesis. A potential role for post-exposure prophylaxis of leprosy in reducing M. leprae-induced anti-inflammatory mediators and, in consequence, Treg/T effector ratios is proposed.